Cruelty and laughter : forgotten comic literature and the unsentimental Eighteenth Century - Dickie, Simon (University of Chicago Press, 2011)
Eighteenth-century British culture is often seen as polite and sentimental-the creation of an emerging middle class. Simon Dickie disputes these assumptions in Cruelty and Laughter, a wildly enjoyable but shocking plunge into the forgotten comic literature of the age. Beneath the surface of Enlightenment civility, Dickie uncovers a rich vein of cruel humor that forces us to recognize just how slowly ordinary human sufferings became worthy of sympathy. Delving into an enormous archive of comic novels, jestbooks, farces, variety shows, and cartoons, Dickie finds a vast repository of jokes about cripples, blind men, rape, and wife-beating. Epigrams about syphilis and scurvy sit alongside one-act comedies about hunchbacks in love. He shows us that everyone-rich and poor, women as well as men-laughed along. In the process, Dickie also expands our understanding of many of the century's major authors, including Samuel Richardson, Lady Mary Wortley Montagu, Tobias Smollett, Frances Burney, and Jane Austen. He devotes particular attention to Henry Fielding's Joseph Andrews, a novel that reflects repeatedly on the limits of compassion and the ethical problems of laughter. Cruelty and Laughter is an engaging, far-reaching study of the other side of culture in eighteenth-century Britain.